Introduction of the Uppsala Traumatic Brain Injury register for regular surveillance of patient characteristics and neurointensive care management including secondary insult quantification and clinical outcome. (August 2013) - Nyholm, Lena; Howells, Tim; Enblad, Per; Lewén, Anders
Abstract Background. To improve neurointensive care (NIC) and outcome for traumatic brain injury (TBI) patients it is crucial to define and monitor indexes of the quality of patient care. With this purpose we established the web-based Uppsala TBI register in 2008. In this study we will describe and analyze the data collected during the first three years of this project. Methods. Data from the medical charts were organized in three columns containing: 1) Admission data; 2) Data from the NIC period including neurosurgery, type of monitoring, treatment, complications, neurological condition at discharge, and the amount of secondary insults; 3) Outcome six months after injury. Indexes of the quality of care implemented include: 1) Index of improvement; 2) Index of change; 3) The percentages of 'Talk and die' and 'Talk and deteriorate' patients. Results. Altogether 314 patients were included 2008–2010: 66 women and 248 men aged 0–86 years. Automatic reports showed that the proportion of patients improving during NIC varied between 80% and 60%. The percentage of deteriorated patients was less than 10%. The percentage of Talk and die/Talk and deteriorate cases was <1%. The mean Glasgow Coma Score (Motor) improved from 5.04 to 5.68 during the NIC unit stay. The occurrences of secondary insults were less than 5% of good monitoring time for intracranial pressure (ICP) >25 mmHg, cerebral perfusion pressure (CPP) <50 mmHg, and systolic blood pressure <100 mmHg. Favorable outcome was achieved by 64% of adults. Conclusion. The Uppsala TBI register enables the routine monitoring of NIC quality indexes.